Increasing Savory Potatoes and Queen Mango Bengkalis Msme’s Performance Through Entrepreneurship, And Digital Marketing at Polbeng Business Expo Chapter II - Umi Kurnia Wati; Muhammad Fuad Asrofillah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Micro, Small, and Medium Enterprises (MSMEs) serve as a fundamental pillar for Indonesia's economic development, particularly by driving job creation and bolstering regional economic stability. Despite their importance, many culinary-focused MSMEs in Bengkalis Regency encounter significant obstacles regarding effective entrepreneurship practices and the integration of digital marketing tools. This research investigates the strategic implementation of entrepreneurship and digital marketing tactics utilized during the Polbeng Business Expo, assessing their impact on the performance of two local ventures: Savory Potatoes and Queen Mango. Adopting a descriptive qualitative approach, this study employs data gathered through direct observation, documentation, and the analysis of sales records collected throughout the three-day exhibition period. The analysis focuses on critical entrepreneurial competencies, including product innovation, opportunity identification, and customer service excellence, while simultaneously evaluating digital marketing strategies such as social media campaigns and the adoption of modern digital payment systems. The findings demonstrate that the deliberate application of these strategies significantly improved sales performance, broadened customer reach, and enhanced product visibility. The successful integration of entrepreneurial initiatives with robust digital marketing within a structured event environment effectively strengthened the competitiveness of these MSMEs. Ultimately, this research offers actionable insights for future MSME development, providing a scalable framework that supports sustainable local economic growth and improved market resilience within the vibrant Bengkalis Regency area.